Acute Central Retinal Vein Occlusion Secondary to Reactive Thrombocytosis after Splenectomy. (8th September 2014) - Oncel Acir, Nursen; Borazan, Mehmet; Dadaci, Zeynep
Abstract : The diagnosis and treatment of central retinal vein occlusion was reported in a young patient. Central retinal vein occlusion was probably related to secondary to reactive thrombocytosis after splenectomy. The patient was treated with steroids for papilledema and administered coumadin and aspirin. The symptoms resolved, and the findings returned to normal within three weeks. Current paper emphasizes that, besides other well-known thrombotic events, reactive thrombocytosis after splenectomy may cause central retinal vein occlusion, which may be the principal symptom of this risky complication. Thus, it can be concluded that followup for thrombocytosis and antithrombotic treatment, when necessary, are essential for these cases.